FATS AND FIBERS CONSUMPTION IN THE FOOD BEHAVIOR OF PHYSICAL EDUCATION PEDAGOGY STUDENTS AND EMPLOYEES OF THE UNIVERSIDAD AUTÓNOMA DE CHILE, TALCA, CHILE. (Fiep Bulletin - online, 2017)
Healthy eating presents a balance of foods and beverages within the energy needs, in place of any food or food.Eating habits are dynamic and influenced by many factors, including food tastes and preferences, weight problems, physiology,time and convenience, the environment, abundance of food, economics, media / marketing , Perceived product safety, cultureand attitudes / beliefs. Objective: To analyze the consumption of fats and fibers in the eating behavior of Pedagogy students inPhysical Education and Staff of the Autonomous University of Chile, Talca, Chile. Methodology: descriptive, cross-sectionalstudy; Instrument: Simplified Food Frequency Survey (fats and fibers). Shows employees: 51 subjects (34 women, 17 men);Average age: 38.4 years, staff and professors from various departments and courses, administrative and support; It showsstudents: 159 subjects (56 women, 103 men); Average age: 21.45 years, students of all levels of the Pedagogy course in PhysicalEducation; Descriptive frequency analysis. Consumption of fats (high = negative) and fibers (low = negative) variables importantfor good nutrition. Results: comparing the two groups, both presented low fat consumption and also very low fiber consumption.Most consumed fibers: salad leaves, conventional breads, vegetables and fruits. Both groups present low intakes of whole grainsand whole grains, with the group of students presenting values higher than the employees in this variable. The most consumedfats in two groups are related to cheeses and curd cheese, eggs, “sopaipillas”, sausages, margarine, mayonnaise, fatty meatsand fries. Conclusions: adult individuals present basically the same eating behavior in relation to consumption of fats and fibersas university students. Perhaps the university environment is a factor that directly interferes in the nutritional habits of bothgroups, even if the groups that present a daily life of activities mostly differentiated. The fats consumed indicate the frequentconsumption of fast food by both groups. Students of Physical Education consume whole grains in percentage higher than theemployees.
Keywords: Food behavior; fat; fiber; Pedagogy in Physical Education; employees; Autonomous University of Chile